Systemic thinking for public managers : five practices for creating a vibrant organization - Murphy, Sheila, Ph. D.; Regenold, Tracey A.; Reed, Philip A. (New York, NY : Routledge, 2024)
"Offering a pathway to vibrant organizations, this book integrates systems thinking, critical thinking, and design thinking, and provides the tools needed to proactively apply them in the social systems where we live and work. Systemic thinking-the combination of systems thinking, critical systems thinking, and design thinking-provides a way of addressing the complexity of problems faced by public sector managers. Far too often systemic thinking has been discussed theoretically rather than practically. This book changes that, enabling public sector managers and leaders to connect staff, partners, and stakeholders in the pursuit of thoughtfully designed and responsive service. Clearly written and designed to be put to immediate use on the job, each chapter provides a discussion of one a specific practice. Included are guiding principles, a case study, relevant practical tools, and suggestions of for additional practice and reading. Using this book, managers of social systems such as public welfare, healthcare, public schools and libraries, housing and community development, and students of public administration will gain a deeper understanding of organizational systems and design, and a new toolkit to fortify their own organizations"--
Keywords: Industrial management; Critical thinking; System theory; Strategic planning; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Decision-Making & Problem Solving